(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
With the rapid advancement of technology and the advent of the internet, journalism has undergone a transformative shift in recent years. The emergence of online platforms and social media has given rise to new genres of journalism, each with its own distinct characteristics and impact on the media landscape. This article focuses on the origin of modern genres in internet journalism, using national journalism as a case study. By examining the evolution of national journalism in the digital era, we aim to shed light on the factors that have shaped its development and explore the implications for the future of journalism.